Peran Transparansi Pengelolaan Keuangan dalam Meningkatkan Motivasi Kerja Guru SMK - Baihaqi, Muhammad Affan; Harsono, Harsono; Suyatmini, Suyatmini (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the role of financial management transparency in improving the work motivation of vocational high school (SMK) teachers in Sragen Regency. The research employed a quantitative approach with an ex post facto correlational design. The population consisted of 100 private vocational high school teachers, all of whom were selected as research respondents using the total sampling technique. Data were collected through closed-ended questionnaires using a four-point Likert scale. The financial management transparency variable was measured through indicators of information disclosure, data accessibility, report clarity, stakeholder participation, and accountability, while teacher work motivation was measured through responsibility, recognition, job satisfaction, work enthusiasm, and commitment indicators. Data analysis was conducted using descriptive statistics and simple linear regression analysis with the assistance of SPSS software. The results showed that both financial management transparency and teacher work motivation were categorized as very high. Regression analysis indicated that financial management transparency had a positive and significant effect on teacher work motivation, with a significance value of 0.000 < 0.05 and an R Square value of 0.541. These findings indicate that transparent financial management can strengthen teachers’ trust, sense of fairness, and organizational commitment, thereby increasing their work motivation in vocational schools.